Akuntansi lingkungan: suatu tinjauan pemanfaatan eco enzyme untuk pengobatan Penyakit Mulut dan Kuku (PMK) sapi di Malang - Jamaluddin Jamaluddin; Sri Mintarti; Rita Damayanti; Yudi Hartono; Randhi Akhdiyat (Proceeding of National Conference on Accounting & Finance, 2023)
The first objective of this study was to determine the effectiveness of using eco-enzyme for treating nail and mouth disease (NMD) in cattle from the perspective of environmental accounting. The second is to find out the advantages and disadvantages of using eco-enzyme, and the third is to know the cost of production for making eco-enzymes. This eco-enzyme results from the fermentation of household organic waste, sugar, and water. Eco enzyme is environmentally friendly and has an impact on improving the quality of the environment. This type of research is a mixed method with a case study approach. This research was conducted in Malang because, in that area, there were cases of NMD which were treated using eco-enzyme. The results showed that the use of eco enzymes for the treatment of NMD was very effective. They can be seen from the cure rate of NMD treated with eco enzyme reaching 100%. The use of eco enzymes is highly recommended for the treatment of NMD, and to educate the public to protect the environment by using eco enzymes.